Sensitivity analysis of the knee ligament forces to the surgical design variation during anterior cruciate ligament reconstruction: a finite element analysis. Issue 9 (4th July 2022) - Adouni, Malek; Faisal, Tanvir R.; Dhaher, Yasin Y.
Abstract: The purpose of this study is to understand the effect of essential surgical design parameters on collateral and cruciate ligaments behavior for a Bone-Patellar-Tendon-Bone (BPTB) anterior cruciate ligament reconstruction (ACL-R) surgery. A parametric finite element model of biomechanical experiments depicting the ACL-R surgery associated with a global sensitivity analysis was adopted in this work. The model parameters were six intraoperative variables, two-quadrant coordinates of femoral tunnel placement, femoral tunnel sagittal and coronal angles, graft pretension, and the joint angle at which the BPTB graft is tensioned (fixation angle). Our results indicated that cruciate ligaments (posterior cruciate ligament (PCL) and graft) were mainly sensitive to graft pretension (23%), femoral tunnel sites (56%), and the angle at which the surgeon decided to fix the graft (14%). The collateral ligaments (medial and lateral) were also affected by the same set of surgical parameters as the cruciate ligaments except for graft pretension. The output data of this study may help to identify a better role for the ACL-R intraoperative variables in optimizing the knee joint ligaments' postsurgical functionality.